Relative Nutritional And Phytochemical Composition Of Citrus Fruit Compartments- A Case Against Wasting Citrus Peels - Batool, Aniba; Imran, Samra; Tanweer, Afifa (Nurture, 2020)
Citrus fruits are known to contribute towards health considering their nutritional composition as well as bioactive ingredients. Although utilized at the industrial level, household-level consumption of citrus peel is not a common concept. The current study was conducted to compare the composition of different citrus fruits as well as to compare their peels and pulps composition. Three samples of citrus fruits (oranges (Citrus Sinensis) [sample O], lemons (Citrus Limons) [sample L], and grapefruits (Citrus Paradisi) [sample G]) were selected. Two variables; type of fruit with three categories (O vs L vs G) and part of the fruit with two categories (peel vs pulp) were studied. Proximate contents (AOAC methods), antioxidant activity (modified DPPH bleaching), Ferrous ion chelating activity, and total phenol content (Folin- Ciocalteu method) were determined for each sample. Oneway ANOVA and post hoc analysis was run to note down differences among various samples. Except for moisture and fat, all other proximate components showed significantly higher amounts in peels compared with pulp. Fiber and ash contents were significantly higher in peels compared with pulps for all three fruits with a mean difference of L=10.1g, O= 9.29g, G= 10.19g for fiber and L= 0.18g, O=0.37g, G=0.10g for ash. Protein and carbohydrate were found in higher quantity in peels of Samples O and L (mean difference L=0.38g, O=0.15g for protein and L=8.1g, O=13.86g) while significantly lower in the peel of sample G (mean difference protein=1.14g, carbohydrate=0.98g). Antioxidant capacity, total phenolic content and chelating activity were found to be significantly higher in peels of L, O, and G though these contents were not significantly correlated (p>0.05) to one another. The findings of this study show that citrus fruits are a rich source of nutrients as well as phytochemicals. The peels of citrus fruits can serve as better sources of antioxidants, phenolic content, chelating properties, and some nutrients than their pulps. This study provides evidence for the benefits of utilizing peels at the household level while reducing food waste.